WELFARE REFORMS IN CENTRAL AND EASTERN EUROPE: A NEW TYPE OF WELFARE REGIME? - Aidukaite, Jolanta (Ekonomika, 2010)
This paper discusses some recent socio-economic achievements and losses in Central and Eastern Europe from a comparative perspective. Yet, the paper examines whether the economic-social-political restructuring of Central and Eastern Europe and the ensuing social policy reform has brought new forms of welfare regimes into focus. The paper demonstrates that, despite an increase in poverty and inequalities in many Central and Easter European countries during the last 18 years, the social policy systems have not experienced a radical dismantlement throughout the entire region and still show more comprehensive solutions to social problems than residual ones. Furthermore, the Central and Eastern European region is very diverse regarding the scope and depth of social problems encountered, and some countries have implemented more successful policy solutions than other ones. Nevertheless, the experience of the communist regime, the relatively lower fiscal capacity of the states as well as the higher share of GDP produced in the shadow economy allow the Central and Eastern European countries to group into a distinct post-communist regime. The current global economic crisis, which is felt in the CEE region much more than in the rest of the globe, can reinforce the features of the post-communist welfare model: still quite comprehensive in its structures, but weak in its performance to ensure a decent standard of living for its citizens.